Single motherhood and (un)equal educational opportunities: Evidence for Germany - Philippe Mahler; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2005)
We examine the effect of single motherhood on children's secondary school track choice using 12-year-old children drawn from the German Socio-Economic Panel. In line with previous studies for the U.S., the U.K. and Sweden, we find a negative correlation between single motherhood and children's educational attainment. Looking for alternative explanations for this correlation, we use probit regression models to control for factors related to single motherhood such as higher educational background, lower household income and higher labor supply of the mother. Our evidence suggests that single motherhood reduces school attainment mainly because it is associated with lower resources (household income) available for the child.
Keywords: I21; J12; 330; school choice; educational attainment; binary response model; German Socio-Economic Panel; Bildungsniveau; Alleinerziehende; Kinder; Bildungschancen; Schätzung; Deutschland